The Effect of Web View and Prices on Buying Interest in E-Commerce Shopee with Trust as a Mediation Variable (Case Study on Shopee Users in Maros Regency) - Tri Jayanti thohir; Bambang Widagdo; Marsudi Marsudi (Business Innovation Management and Entrepreneurship Journal, 2022)
This study examines and analyzes the effect of web display and price on buying interest in e-commerce Shope through trust as a mediating variable. The type of research used is explanatory research with survey methods and quantitative approaches and data collection using a questionnaire to 100 respondents to Shopee users in Maros Regency, South Sulawesi. The collected data was then analyzed using SmartPLS 3. The results showed that the price and trust web display positively and significantly affected buying interest. Web appearance and price have a positive and significant effect on trust. Then web appearance and price have a positive and significant effect on buying interest through trust as a mediating variable.